Anatomical Variations of Renal Arteries and Their Clinical Implications in Urological and Transplant Surgeries: A Systematic Review: Renal Artery Variations: Clinical Implications - Khatoon, Shehla; Mehreen, Tahira; Jan, Muhummad Adnan; Shah, Syed Mohammad Tahir; Khan, Abdul Hafeez; Bukhari, Anila Shah (Pakistan Journal of Health Sciences, 2025)
Anatomical variations of the renal arteries are frequent and can complicate urological and transplant procedures. However, contemporary evidence on their prevalence and clinical implications remains fragmented. Objectives: To systematically review studies published between 2019 and 2025 that report renal artery variants and evaluate their surgical impact in urology and transplantation. Methods: This review was conducted following PRISMA 2020 guidelines. A systematic search of PubMed, Scopus, and Cochrane identified original human studies reporting quantitative data on accessory arteries, early branching, or unusual origins. Fifteen eligible studies were included in the final synthesis. Risk of bias was assessed using the Joanna Briggs Institute checklist for imaging studies and the Newcastle–Ottawa Scale for surgical cohorts. Risk of bias across imaging and surgical studies was rated low to moderate based on JBI and NOS appraisal. Results: The prevalence of accessory renal arteries and early branching varied widely, ranging from 10% to over 30% across populations. A recent donor CTA study reported accessory arteries in 25.6% and early branching in 17%, while a contemporary Omani series found more than 30% of kidneys with multiple arteries. In transplant cohorts, grafts with multiple renal arteries achieved outcomes comparable to those with single arteries when appropriate reconstruction was performed. Microsurgical and vascular techniques have enabled the successful management of complex arterial anatomy without compromising graft function. Conclusions: Renal artery variations are common and clinically important. Preoperative CT angiography remains the gold standard for differentiating true multiple arteries from early branches, ensuring safe surgical planning.